PROMOSI DAN PELAYANAN SEBAGAI STRATEGI MEMPERTAHANKAN USAHA PADA TOKO RITEL DI SUKABUMI - Hanipah Hanipah; Zeffanya Raphael Wijaya (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
The purpose of this study is to see and analyze how a retail business maintains its business, including maintaining customer loyalty. The research was conducted at a retail store in Sukabumi. Methods of data collection is done through observation and interviews with resources in the store. The results showed that: 1) retail stores in maintaining their business utilize various promo modules and involve the active role of all resources in the store; 2) retail stores provide all the best to consumers, through an attitude that prioritizes 5S, and strives to meet every consumer need, so as to maintain consumer trust and loyalty; 3) the ability to promote and good service makes retail stores can compete with competitors and can maintain their business.